Persistent hypertension after preeclampsia in a group of Cameroonians: Result of a cross‐sectional study and perspectives to reduce its burden in Limited Income Countries. Issue 6 (7th May 2021) - Nganou‐Gnindjio, Chris Nadège; Kenmogne, Denise; Essama, Doris Bibi; Nkeck, Jan Rene; Yanwou, Nathan; Foumane, Pascal
Abstract: Preeclampsia/eclampsia significantly increases the risk of future hypertension. Several factors may be involved in this process. The purpose of this study was to identify them in Cameroonians. We conduct a cross‐sectional study including women aged 18 to 45 years, who deliver between December 2011 and 2016, and were diagnosed and followed up for preeclampsia/eclampsia in two major obstetrical and gynecologic units in Yaoundé (Cameroon). Those with persistent high‐blood pressure after 6 months were classified as persistent hypertension (PH). Associated factors were investigated using multivariate analysis with logistic regression and presented with an adjusted odds ratio (aOR) and the 95% confidence interval. 92 participants were included, with 30 (32.6%) with PH. The independent factors associated with PH were as follows: maternal age during preeclampsia above 30 years (aOR = 6.30 [1.1; 35.4], p = .03), at least five deliveries prior preeclampsia (aOR = 1.50 [2; 6.6], p = .008), and family history of diabetes (aOR = 14.8 [2.6; 85.7], p = .003). About one in three women with preeclampsia/eclampsia will have PH. The clinician needs to pay more attention to the potential risk factors identified above. More appropriate strategies need to address the burden of this condition in the context of low resources. Abstract : In Cameroon, about one in three women with preeclampsia/eclampsia will have persistent hypertension. The clinician needs to pay more attention to those patients, especially in case of maternal age during preeclampsia above 30 years, at least 5 deliveries prior preeclampsia and family history of diabetes. More appropriate strategies need to address the burden of this condition in the context of low income countries.